What Are the Limitations of AI in Mental Health Care? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Artificial intelligence (AI) is rapidly transforming various sectors, and mental health care is no exception. AI-powered tools, such as chatbots and predicti...
Keywords: AI in Mental Health; Limitations; Mental; Health; Artificial Intelligence; Healthcare; Digital Health